2009
DOI: 10.1007/s11431-009-0266-2
|View full text |Cite
|
Sign up to set email alerts
|

LES/FDF simulation of particle dispersion in a gas-particle two phase plane wake flow

Abstract: A filtered density function (FDF) transport equation was derived for the fluid velocity seen by the particles in gas-particle two-phase flow. An LES/FDF simulation of a two-phase plane wake flow was carried out. The simulation results were compared with both the experimental photograph and the simulation results without using the FDF model, and proved that the LES/FDF model can clearly improve the spatial dispersion of the particle phase. multiphase flow, turbulence, numerical simulation, large eddy simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…An LES/FDF (Jin et al, 2009 model based on the consistent probability theory was developed by the authors to describe the interaction between the two phases. In this model, LES is used to model the fluid flow and an FDF transport equation is derived to solve the sub-grid scale eddies seen by the particles.…”
Section: Introductionmentioning
confidence: 99%
“…An LES/FDF (Jin et al, 2009 model based on the consistent probability theory was developed by the authors to describe the interaction between the two phases. In this model, LES is used to model the fluid flow and an FDF transport equation is derived to solve the sub-grid scale eddies seen by the particles.…”
Section: Introductionmentioning
confidence: 99%
“…[64], Lu et al demonstrated LES/PDF with realistic chemistry capability of simulating turbulent combustion by incorporating in-situ adaptive tabulation (ISAT) into a structured LES code [37] with a Lagrangian Monte Carlo implementation of the composition PDF method. Jin et al [68][69][70] applied LES/PDF for gas-particle two-phase flow, studying on the SGS influence on the prediction of particle motion. Transported velocity-scalar joint PDF equations are further derived for the flow field "seen" by droplets or particles, achieving the LES-VSJFDF model for multi-phase flow.…”
Section: Pdf As a Subgrid Model For Lesmentioning
confidence: 99%
“…ρ f is the fluid density, U f and U p are the vector velocities of the fluid and particles, respectively. For the gas-particle two-phase flow field, the "velocity filtered density function" (VFDF) of the gas phase "seen" by the particles, denoted by P L , can be defined by [8] ( ; , )…”
Section: Governing Equation For Two Phases and Transport Equation Of mentioning
confidence: 99%
“…In this model, a filtered density function (FDF) transport equation was derived for the fluid velocity seen by the particles, which was perfectly simulated in the framework of filtered density function (FDF) [8]. In this paper, the parameter of particle dispersion rate was used to make a further investigation on the effect of SGS turbulence on particle motion with the developed LES/FDF model.…”
Section: Introductionmentioning
confidence: 99%